Enhancing forecasting and earth observation data and applications for drylands - Jameel Observatory for Food Security Early Action (International Livestock Research Institute, 2025)
Video recordiing of the session at the IGAD Centre for Pastoral Areas and Livestock Development (ICPALD), the Jameel Observatory for Food Security Early Action and the Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) Programme 'Building the Resilience and Prosperity of Pastoralists and Dryland Communities' research and policy dialogue in Nairobi on 1 and 2 October 2025.